Application of Behaviorist Theory Based on the Learning Experience of Students in Boarding School Environments - Zainal Abidin Muhja; Meliani Indria Wijaya (Al-Hayat: Journal of Islamic Education, 2024)
This study examines the importance of implementing behaviourist theory in student learning. It examines student responses and the role of the educational environment in implementing behaviourist theory at the Ar-Rifa'ie Tarakan Islamic Boarding School. The approach used in this study is qualitative, the type is descriptive and ethnographic. Data collection uses in-depth interviews and observations. The validity of the researcher's data uses source triangulation. The analysis adopts the Miles & Huberman model, which includes data collection, reduction, delivery, and conclusion. The study's results indicate that applying behaviourist learning theory uses reinforcement, motivation, incentives, and practice. Activities that utilize behaviourist learning theory include dhuha prayer, reading the Qur'an and tahfidz, Friday prayers, and muhadoroh (speaking practice). This is because the behaviourist or behavioural learning theory shows when students' behaviour changes in a positive direction, they become more motivated to learn and interact, and their memory and tolerance become stronger. The educational environment influences student behaviour and development, including climate, geographical location, habitat, and customs. This study only relies on behaviourist learning theory to explain changes in student behaviour. This may ignore other relevant educational approaches, such as cognitivism or constructivism theory, which can provide additional perspectives on developing students' learning. This study integrates behaviourist learning theory with students' religious activities, which is a unique approach because behaviourism is generally more often applied in the context of general education than religious education.